2016
DOI: 10.1063/1.4944839
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime degradation and regeneration in multicrystalline silicon under illumination at elevated temperature

Abstract: We examine the carrier lifetime evolution of block-cast multicrystalline silicon (mc-Si) wafers under illumination (100 mW/cm2) at elevated temperature (75°C). Samples are treated with different process steps typically applied in industrial solar cell production. We observe a pronounced degradation in lifetime after rapid thermal annealing (RTA) at 900°C. However, we detect only a weak lifetime instability in mc-Si wafers which are RTA-treated at 650°C. After completion of the degradation, the lifetime is obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 12 publications
7
92
1
Order By: Relevance
“…Nevertheless, the largest degradation is observed in the non‐textured edges of the SiN x ‐passivated b‐Si cells, which is an interesting finding and will be discussed later in more detail. Finally, Figure C reveals that the degradation is rather uniform laterally in good grain areas, which is characteristic of LeTID . However, defect clusters show slightly stronger LeTID, as reported recently, which is even more pronounced in the acidic‐textured cells (Figure E,F).…”
Section: Resultssupporting
confidence: 80%
“…Nevertheless, the largest degradation is observed in the non‐textured edges of the SiN x ‐passivated b‐Si cells, which is an interesting finding and will be discussed later in more detail. Finally, Figure C reveals that the degradation is rather uniform laterally in good grain areas, which is characteristic of LeTID . However, defect clusters show slightly stronger LeTID, as reported recently, which is even more pronounced in the acidic‐textured cells (Figure E,F).…”
Section: Resultssupporting
confidence: 80%
“…24, we find an average Cu concentration of ∼7 × 10 13 cm 3 in the reference samples with no emitter, which approximately corresponds to the Cu contamination levels reported by several authors in as-cut solar-grade wafers. 1,12,25 In Group A, the residual Cu concentration after gettering is estimated to be ∼3.8 ×10 13 cm 3 (i.e. a gettering efficiency < 50%).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that high temperature steps during cell processing are influencing the strength of this degradation, and that they can be minimized by an effective external gettering [26]. It could also be shown that the firing step has a strong influence on LeTID strength, and that it can be minimized by applying a co-firing step at lower temperature [27], [28]. Recently, it could be demonstrated that an additional second firing step at lower peak temperature can significantly reduce the LeTID strength, and it was pointed out that although LeTID can be reduced, cell efficiency (series resistance) might be affected by this second lower temperature firing step [29].…”
Section: E Consequences For Mc-si Degradation Phenomenamentioning
confidence: 99%